Modified coke breeze distribution in iron ore sintering - a novel technique of reducing energy consumption and improving quality - PAL, JAGANNATH; Prasad, Dhirendra; Venugopalan, T (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
In normal sintering of iron ore, there is a wide difference in temperature of sinter bed between top and bottom; i.e. the flame front temperature of sinter bed gradually increases towards the bottom because, lower part gets longer time for drying and preheating by exit gas.  Therefore, the top part may have insufficient fusion and bottom is excessively fused. Thus, sinter quality may become inhomogeneous and the coke breeze requirement becomes higher than the actual thermal requirement. If it is charged in multiple layer; i.e. higher, coke at the top and lower amount of coke at the bottom, heat will be homogeneously distributed and actual coke requirement would be lower than the existing. However, no study has done so far on this. Therefore, the current study explores the possibility of reducing energy consumption in iron ore sintering by reducing coke ratio from top to bottom without deteriorating the sinter property. 12% reduction in coke breeze rate has been found and the sinter quality has been improved by use of triple layer of sinter mix with lower coke rate towards the bottom. Further, when 5% oxygen has been enriched in suction gas along with using triple layer of sinter mix, up to 18% reduction in coke breeze has been found.
Keywords: coke breeze, multiple layer, energy consumption, oxygen enrichment